A 3-week feed restriction after weaning as an alternative to a medicated diet: effects on growth, health, carcass and meat traits of rabbits of two genotypes. (21st December 2016) - Alabiso, M.; Di Grigoli, A.; Mazza, F.; Maniaci, G.; Vitale, F.; Bonanno, A.
Abstract : Feed restriction after weaning is widely used in meat rabbit farms to promote health and reduce mortality, but this practice impacts negatively on rabbit growth and slaughter performance. This study compared a 3-week post-weaning feed restriction with ad libitum medicated feeding, evaluating effects on feed intake, growth, health, carcass and meat quality of rabbits of two genotypes: Italian White pure breed and Hycole hybrid×Italian White crossbred. A total of 512 rabbits at 36 days of age, of both sexes and two genotypes, were divided into four homogeneous groups assigned, from 36 to 57 days of age, to different feeding programmes (FP): restricted non-medicated (R-N), ad libitum non-medicated (L-N), restricted medicated (R-M) and ad libitum medicated (L-M). The diets were medicated with oxytetracycline (1540 mg/kg) and colistin sulphate (240 mg/kg). The restriction, performed by giving 70, 80 and 90 g/day of feed for the 1st, 2nd and 3rd week, was followed by ad libitum feeding in the successive 5 weeks, up to slaughter at 92 days of age. Restricted feeds were ingested at a level of 64% of the feed intake recorded in the ad libitum fed rabbits; it was significantly associated, regardless of medication and rabbit genotype, with a lower feed intake (−22 to −24 g dry matter/day) during the entire experiment, compensatory growth and a lower feed conversion ratio in the ad libitum period, and a lower final live weight (−150 g) than ad libitum feeding ( P <0.001). During restriction, mortality was lower in the restricted rabbits (6.25%, 5.47% v . 12.5%, 14.8% for R-N, R-M, L-N and L-M; P <0.05), whereas in the ad libitum period mortality did not differ among the groups (9.23%, 9.90%, 11.0% and 4.59% for R-N, R-M, L-N and L-M). Dressing out percentage was not affected by FP or genotype; heavier carcasses were produced by rabbits fed ad libitum (+100 g; P <0.001) and crossbred rabbits (+122 g; P <0.001). Restriction did not alter meat quality, except for a tendency towards a higher cooking loss and less fat; crossbred meat was higher in L * (+1.3; P <0.01) and b * (+0.51; P <0.05) colour indexes and tenderness (−0.14 kg/cm 2 ; P< 0.05) than pure breed meat. Under the conditions of this study, a 3-week restricted feeding after weaning resulted to be a suitable alternative, also for high growth potential genotypes, to the antibiotics to preserve rabbit health. The production of lighter carcasses could be compensated partly by the lower feed conversion ratio showed by restricted rabbits.